2001
DOI: 10.1039/b008616i
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical exploitation of quinone–thiol interactions: application to the selective determination of cysteine

Abstract: Square wave voltammetry was applied to the detection of cysteine through the use of an indirect assay that exploits the reaction of the thiol with a quinone indicator. Voltammetric discrimination between unreacted quinone and the corresponding quinone-cysteine adduct is possible with clear resolution of the latter peak providing a linear response from 5 to 47 microM. The selectivity of the approach was assessed with no interference from cystine, lysine, paracetamol or 4-aminophenol. The response recorded in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Square wave voltammetric techniques allowed electrochemical processes due to the unreacted orthoquinone and the accumulated adduct species to be resolved such that the latter could be effected as a means of quantifying cysteine [95]. A second reaction process relying upon the reaction of various quinone structures with cysteine has also been detailed [26]. It was found that through analysing the electrochemical reduction sweep that the quinone and the quinone-cysteine reduction peaks were spatially resolved.…”
Section: Derivatization Detectionmentioning
confidence: 99%
“…Square wave voltammetric techniques allowed electrochemical processes due to the unreacted orthoquinone and the accumulated adduct species to be resolved such that the latter could be effected as a means of quantifying cysteine [95]. A second reaction process relying upon the reaction of various quinone structures with cysteine has also been detailed [26]. It was found that through analysing the electrochemical reduction sweep that the quinone and the quinone-cysteine reduction peaks were spatially resolved.…”
Section: Derivatization Detectionmentioning
confidence: 99%
“…23 Therefore, many researches have been focused on the determination of cysteine in pharmaceuticals, urine, serum, and plasma. [24][25][26][27][28][29] Although HPLC 26 and electrochemical analyses 27 are versatile for determining cysteine, they require expensive equipment. Spectrophotometry 28,29 and flourometry, 30 which are rather ubiquitous techniques, are alternatives, but their poor selectivity and laborious procedures have limited their application.…”
Section: Introductionmentioning
confidence: 99%
“…As 89.3% of human proteins and 17% of their tryptic peptides possess at least one cysteine [59], the proposed methodology was targeted toward cysteine mass tagging. Based on recent works on the electrochemical detection of sulfides [60,61], thiols [62], and cysteine [63,64] with quinone derivatives, we focused on the potential use of electrogenerated benzoquinones (coming from the oxidation of hydroquinones) able to react specifically with cysteine residues during electrospray mass spectrometric measurements. We present below a review of the different steps of the development of on-line electrochemical probes for cysteine mass tagging, from the proof of principle [65] to the elucidation of the tagging reaction mechanism [66], characterization of the microspray design influence on the tagging process [67], search for an optimal electrochemical probe [68], and final application to protein identification [69].…”
mentioning
confidence: 99%